Towards an Islamic Law for Muslims in Malaysia - Ibrahim, Ahmad (Journal of Malaysian and Comparative Law, 2019)
The Federal Constitution provides that "Islam is the religion of the Federaion; but other religions may be practised in peace and harmony in any part of the Federation".